Tabung Haji as an Islamic financial institution for sustainable cconomic development - Ishak, Mohd. Shuhaimi (2011)
Tabung Haji (TH) is a short synonym for Lembaga Urusan dan Tabung Haji Malaysia (The Pilgrims Management and Fund Board of Malaysia) started its operation in 1963 to assist the Muslim/rural community in Malaysia with the financial costs of performing the hajj to Saudi Arabia. TH acts as an institution of savings for Muslims to fulfill their religious obligation. This research attempts to highlight TH as a role model of an Islamic financial institution for economic development. The research aims to show the significance of TH by analysing its business activities and their financial performances to illustrate that it is a viable business entity for sustainable economic development. Keywords: TH, Pilgrimage, Islamic Financial Institution, Depositors and Sustainable Economic Development